Steel corrosion - induced concrete cracking / Yuxi Zhao, Weiliang Jin - Zhao, Yuxi
This book presents the latest advances in the origin, mechanism and development of corrosion-induced cracking in concrete. It investigates topics including expansion coefficient and elastic modulus of steel corrosion, rust layer and rust distribution, spatial distribution of corrosion products, the shape of corrosion-induced cracks and so on.